Pre-sport games of soccer and their benefits for students with intellectual limitation (Review) (Revista científica Olimpia, 2021)
In the context of the current transformations of the primary school, the educational inclusion constitutes a priority. The present investigation approaches aspects linked with the integral educational attention to the students with special educational necessities, of intellectual type. On the base of the possibilities that you/they offer the pre-sport games to a better social interaction inside of and outside of the school. The particularities of the article were given in the use of scientific methods of the theoretical levels, fundamental for the revision and analysis. The benefits of the employment of pre-sport games are verified, specifically of soccer, for students with light intellectual limitation. Standing out those mainly related with the work in team, the mutual help and the collective enjoyment.
Keywords: pre-sport games of soccer, light intellectual limitation